Analisis faktor-faktor yang mempengaruhi volume ekspor batubara Indonesia tahun 2015-2020 - Verry Setiyawan Purwanto; Listya Endang Artiani (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2022)
Abstract Purpose – This study was conducted with the aim of analyzing what factors affect the volume of Indonesian coal exports to export destination countries, namely Malaysia, South Korea, China, India and Fillipina from 2015-2020. Methods – The data analysis method used is the panel data regression method with the export volume variable as the dependent variable, and the independent variables are the Gross Domestic Products (GDP) of the destination country, the exchange rate (exchange rate), and the price of coal. Findings – Gross domestic product (GDP) per capita of Malaysia, South Korea, China, Fillipina and has a significant influence on the volume of Indonesian coal exports. The exchange rate has no significant effect on the volume of Indonesia's coal exports. Coal prices of export destination countries have a significant effect on Indonesia's coal export volume Implication – The results of this study have the implication that the internal factors of the main destination countries for Indonesian coal exports in the form of GDP per capita and domestic coal prices determine the volume of Indonesian coal exports. Originality – The contribution of this study was to use panel data from the main destination countries for Indonesia's coal exports. Abstrak Tujuan – Penelitian ini dilakukan dengan tujuan untuk menganalisis faktor apa saja yang mempengaruhi volume ekspor batu bara Indonesia ke negara tujuan ekspor yaitu Malaysia, Korea Selatan, China, India dan Fillipina dari tahun 2015-2020. Metode – Metode analisis data yang digunakan adalah metode regresi data panel dengan variabel volume ekspor sebagai variabel dependen, dan variabel independennya adalah Gross Domestik Products (GDP) negara tujuan, nilai tukar (kurs), dan harga batu bara. Temuan – Gross domestic product (GDP) per kapita negara Malaysia, Korea Selatan, China, Fillipina dan memiliki pengaruh yang signifikan terhadap volume ekspor batu bara Indonesia. Nilai tukar tidak berpengaruh signifikan terhadap volume ekspor batu bara Indonesia. Harga batu bara negara tujuan ekspor berpengaruh signifikan terhadap volume ekspor batu bara Indonesia. Implikasi – Hasil penelitian ini mempunyai implikasi bahwa faktor internal negara tujuan utama ekspor Batubara Indonesia berupa GDP per kapita dan harga batubara domestik menentukan volume ekspor batubara Indonesia. Orisinalitas – Kontribusi penelitian ini adalah menggunakan data panel negara tujuan utama ekspor batubara Indonesia.